2023
DOI: 10.1007/s00705-022-05641-1
|View full text |Cite
|
Sign up to set email alerts
|

A G3P[9] rotavirus strain with an unusual genome constellation in a diarrheic cat in Thailand

Abstract: Rotavirus infection can cause diarrhea in many animal species. A 2-year-old indoor female Siamese cat with bloody mucoid diarrhea tested positive for rotavirus (RV) group A by real-time reverse transcription polymerase chain reaction (RT-PCR). Subsequent conventional RT-PCR amplification of the 11 RV segments and sequencing revealed a G3-P[9]-I2-R2-C2-M2-A3-N2-T3-E3-H3 genome constellation. Phylogenetic analysis showed that the VP4, VP7, NSP1, NSP3, NSP4, and NSP5 genes were closely related to those of human f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…26 However, a similar strain (G3-P[9]-I2-R2-C2-M2-A3-N2-T3-E3-H3) was recently identified in 2021 in Thailand, and was originated from a feline with diarrhoea. 27 The rare combination of G3-P[9]-I2-E3 that was detected in this study is possibly derived from a reassortment event. Reassortment is common among RVs and is a crucial mechanism for the evolution of the virus.…”
Section: Discussionmentioning
confidence: 68%
“…26 However, a similar strain (G3-P[9]-I2-R2-C2-M2-A3-N2-T3-E3-H3) was recently identified in 2021 in Thailand, and was originated from a feline with diarrhoea. 27 The rare combination of G3-P[9]-I2-E3 that was detected in this study is possibly derived from a reassortment event. Reassortment is common among RVs and is a crucial mechanism for the evolution of the virus.…”
Section: Discussionmentioning
confidence: 68%
“…No gene segments of the representative G3P[9] feline/human‐like (FRV‐1/AU‐1‐like) or G3P[3] feline/canine‐like (Cat97/CU‐1‐like) strains shared > 98% nucleotide identity with those of Mie20120017f (Table 1). Among other feline strains, G3P[9] strain THA/Meesuk/2021 most closely resembled Mie20120017f, sharing > 95% nucleotide identity across seven genetic segments (VP4, VP1, and NSP1–5) 32 …”
Section: Resultsmentioning
confidence: 99%
“…THA/Meesuk/2021 most closely resembled Mie20120017f, sharing > 95% nucleotide identity across seven genetic segments (VP4, VP1, and NSP1-5). 32 The VP7 (G6) gene of Mie20120017f shared high nucleotide identity (97.6%-98.0%) and amino acid identity (98.4%-99.5%) with G6P [8] strains identified in Brazil between 2019 and 2022, such as LVCA_30388, AM668, and LVCA_33925 (Table 1). 33 human-like, FRV-1/AU-1-like).…”
Section: Mie20120017f (G6p[9])mentioning
confidence: 99%
“…Rotaviruses can be transmitted as interspecies as a result of genetic reassortment and this situation may result in genetic similarity between rotaviruses that infect different species. There are some examples for interspecies transmission of RVA from bovine to heterologous species, such as from bovine to rabbit (K1130027 strain), from bovine to horse (OH-4 strain) [35,36], and with some recent data, from bovine to feline transmission was shown in other studies [37,38]. It was previously shown that the NSP5 gene of feline RVA strain shares high nucleotide identity with BRV (97%) and it was suggested to have been acquired from a bovine rotavirus through reassortment [38].…”
Section: Declarations Conflict Of Interestmentioning
confidence: 97%
“…In a recent study, the R11-035 strain of a rotavirus, which was transferred from a cat to a human, acquired NSP3 through intergenotype reassortment with strains found in pigs before being transmitted [17]. Phylogenetic analysis of a recent study revealed that some of the genes of the rotavirus (VP4, VP7, NSP1, NSP3, NSP4, and NSP5) were similar to those found in human feline-like rotaviruses, while other genes (VP1, VP2, VP3, VP6, and NSP2) were more similar to those found in human bovine-like rotaviruses [37] The results of this study are consistent with previously published ndings in the area. These results demonstrated that rotaviruses have international, intercontinental and interspecies transmission and Turkish bovine RVA eld isolate can be the source of reassortment that culminates with interspecies transmission.…”
Section: Declarations Conflict Of Interestmentioning
confidence: 99%